Three kings - Roven, Charles; Russel, David O. ([Burbank, Ca.] : Warner Bros. Pictures, 2000)
Absurdly comic tale set after the end of the Gulf War, when three American soldiers looking to plunder stolen gold become involved in an uprising
Executive producer, Kelley Smith-Wait ; editor, Robert K. Lambert ; story, John Ridley
Cast: George Clooney, Mark Wahlberg, Ice Cube
VCD format
Keywords: Persian Gulf War, 1991 -- Drama; Americans -- Iraq -- Drama; Soldiers -- Conduct of life -- Drama